Fabrication of bio composite from bacterial cellulose/starch - Siti Natrah, Ismail (2012)
Bio composite from starch and bacterial cellulose offer good mechanical properties. The objective of this study was to fabricate bio composite from starch, and bacterial cellulose.The research was conducted with 25 samples with difference composition of bacterial cellulose (BC)(0, 7, 14, 21 and 28)wt% and starch(3, 6, 9, 12 and 15)wt%.The bacterial cellulose film produced by Acetobacter xylinum was blend and mixed with starch, and glycerol.The film was characterized by using Universal Testing Machine,water absorption,Fourier Transform Infrared (FTIR),Thermo Gravimetric Analysis (TGA),Scanning Electron Microscopy (SEM) and Soil Burial Degradation,biodegradation by using Aspergillus niger.When the composition of starch and BC increased,the tensile strength and Tensile modulus was increased and the elongation at break was decreased.The absorption of water was increased proportionate with the increasing the composition of bacterial cellulose and starch.From the FTIR test,the bio composite was showed the present of hydroxyl group,C=O stretching(amide I),and C-O bonding.Besides that,TGA showed the thermal degradation of starch and cellulose occurs when the temperature arise to 280°C,leads to depolymerization and to the formation of 1,6-anhydroglucose-ß-Dglucopyranose.Moreover,the SEM analysis showed a smooth and homogenous structure of the film but when the composition of BC increased,the small mat fragments can be saw and the layered structure becomes clearer.The soil burial test and degradation by using Aspergillus niger indicated the degradation rate decreased as the bacterial cellulose content increased.As a conclusion,the film fabricated had a potential application in future to be used as food packaging material because as it had good mechanical properties and biodegradable.In order to improve the properties of bio composite,more research should be done to know the optimum composition of BC and starch should be used to produce the film.Besides that,the study about other alternative material or additive that can be added to the film also can be done to increase the mechanical properties and degradation time.